Implementasi Pola Pembinaan dalam Masa Pengenalan Lingkungan Warga Binaan di Lembaga Pemasyarakatan Kelas II A Banceuy - Renaldy Caesar Adytama Putra (Wajah Hukum, 2020)
Actions of deviations that occur in the community, resulting in many cases of crime that occurred. In this case, there is a need for law enforcement based on laws and regulations, as well as the existence of prison institutions as law enforcement officers. As an effort to overcome social deviations, it is necessary to provide guidance to inmates. The purpose of this study was to determine, the implementation of the program in the initial stages of coaching carried out in the technical implementation unit of Class II penitentiary facilities A Banceuy through a period of environmental introduction (mapenaling) which aims so that new inmates can adjust and recognize their environment so that prisoners can get used to the lifestyle will be served during the criminal period. Mapenaling activities are carried out for approximately 1 (one) month in accordance with PP number 31 of 1999. The research method was conducted using the survey method. The research subjects came from the Correctional Officers who served in the Banceuy Class IIA Correctional Institution. While the object of this research comes from the process of fostering inmates in prison conducted at Class IIA Penitentiary in Banceuy. The informants of this study are correctional officers and correctional residents in Class IIA Penitentiary in Banceuy. This research was conducted through a questionnaire distributed to every citizen fostered by prison and officers in Class IIA Penitentiary in Banceuy. Sources of data come from literature and the field from various books and literature, reports, research journalists and published articles that have relevance to this research. Furthermore, the method of collecting data comes from library data records and then processes the research material. The results of the study indicate that the process of implementing mapenaling is still not optimal and there are several inhibiting factors in the process of implementing mapenaling programs carried out in class IIA correctional facilities